Інновації освітніх компонентів у освітньо-професійній програмі "Охорона праці" на магістерському рівні освіти - Зибнєва, І. В. (Національний технічний університет "Харківський політехнічний інститут", 2025)
В роботі розглянуто інновації освітніх компонентів у освітньо-професійній програмі «Охорона праці» на магістерському рівні освіти. Показаний розподіл обсягу навчального навантаження в кредитах ЕСТS у освітньо-професійній програмі. Надано обґрунтування введення у державну атестацію кваліфікаційну роботу. The paper examines the innovations of educational components in the educational and professional program «Occupational Safety»at the master's level of education. The distribution of the volume of the educational load in ECTS credits in the educational and professional program is shown. The justification for introducing qualification work into the state certification is provided.
Innovations of educational components in the educational and professional program "Occupational safety" at the master's level of education
Keywords: магістерський рівень освіти; освітні компоненти; роботодавці; master's level of education; educational components; employers